PA.29 Trends in the provision of neonatal care in England: changes in patient volume and staffing since 1996. (9th June 2014) - Morgan, AS; Marlow, N; Bennett, CJ; Costeloe, KL; Draper, ES
Abstract : Objective: To investigate effects of changes in neonatal service provision on nurse staffing ratios, admissions and provision of respiratory support (CPAP or mechanical ventilation). Design: Retrospective, cross-sectional surveys of units providing neonatal intensive care (1997) or all care (2006 and 2011) in English maternity units. Results: The response rate was 100% in 1997 and 2006, and 96.4% in 2011 (6 level one units did not respond). The number of whole-time equivalent nurses per cot (WTE/cot) increased between 1997 (0.55 WTE/cot) and 2006 by 0.10 WTE/cot (95% CI 0.06–0.13), and by 0.06 WTE/cot (0.03–0.10) between 2006 and 2011. The ratio of nurses qualified in specialty increased by 0.07 WTE/cot (0.00–0.13) between 1997 and 2006, then by a further 0.05 WTE/cot (0.01–0.09) from 2006 to 2011. The number of admissions per cot was similar in 1995 (41.2) and 2006 (41.9) but increased by 22.7% (10.9–35.9) from 2006 to 2011. Between 1997 and 2006, respiratory support provided increased for each cot by 36.4d (17.5–55.2), and by 1.17d (0.67–1.67) per admission; neither measure changed thereafter. The ratio of babies provided with respiratory support to babies admitted increased from 1997 (0.23) to 2006 by 0.10 (0.07–0.15), by 0.05 (0.2–0.08) from 2006 to 2011, and 0.17 (0.12–0.21) overall. Discussion: Neonatal nursing provision changed little since 1997; in contrast neonatal unit activity, hence intensity of cot use, increased from 1997 to 2011, together with the proportion of babies receiving respiratory support.